Impact of COVID-19 outbreak on mental health and perceived strain among caregivers tending children with special needs. (December 2020) - Dhiman, Sapna; Sahu, Pradeep Kumar; Reed, William R.; Ganesh, G. Shankar; Goyal, Ramesh K.; Jain, Shilpa
Highlights: The COVID-19 outbreak has had a significant impact on caregiver strain compared to perceived strain before the pandemic. Prevalence of depressive symptoms is high among caregivers of children with special needs. Negative perception of homecare therapy is associated with higher perceived strain and poor mental health. Not using tele-rehabilitation and perception of it being a poor medium for rehabilitation pose greater mental health risks. Abstract: Background: While COVID-19 outbreak has had adverse psychological effects in children with special needs, the mental state and burden on their caregivers during this pandemic has yet to be reported. Aims: The objectives of this study were to describe the mental health status and the change in perceived strain among caregivers during the COVID-19 outbreak. Methods and procedures: Two hundred sixty four caregivers completed an online survey that assessed demographics, use and perspective on tele-rehabilitation, homecare therapy, caregiver's strain and mental health. Outcomes and results: The prevalence of depression, anxiety and stress symptoms were found to be 62.5 %, 20.5 % and 36.4 % respectively. A significant difference in caregiver strain ( p  <  0.001, effect size = 0.93) was observed during the outbreak compared to levels pre-outbreak (pre-outbreak strain was measured retrospectively). Caregivers not using tele-rehabilitation along with a perception of it being a poor medium for rehabilitation were at greater risks for poor mental health whereas a negative perception on homecare therapy were strongly associated with higher psychological symptoms and strain. Conclusions and implications: This study identified a high prevalence of depression and significant change in strain displayed by caregivers during the COVID-19 outbreak. We identified several factors associated with poor mental health and perceived strain that can be used to help safeguard caregivers.